2015
DOI: 10.1371/journal.pone.0121436
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Genotype Distribution and Genotype-Specific BCP/preCore Substitutions in Acute and Chronic Infections in Argentina

Abstract: AimIn order to assess Hepatitis B Virus genotype (g) and subgenotype (sg) implications in the course of infection, 234 HBsAg positive patients in different infection stages were characterized (66 acute infections, 63 HBeAg positive chronic infections and 105 anti-HBe positive chronic infections).ResultsOverall, sgA2 (17.9%), gD (20.9%), sgF1b (34.2%) and sgF4 (19.7%) were the most prevalent. Subgenotype F1b was overrepresented in acute and chronic HBeAg infections (56.1%), whereas gD was the most frequent (40.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 70 publications
5
19
3
Order By: Relevance
“…The time-scaled MCCT showed that the three sequences would have a common ancestor dated only four years before the sampling date, suggesting that, unlike the gt-D, the F1b has been recently introduced in Misiones. This is consistent with the current epidemiological data from other regions of Argentina, pointing to this sgt as responsible for most of the acute and new chronic HBV infections (Barbini et al, 2013;Gallego et al, 2014;González López Ledesma et al, 2015;Pezzano et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The time-scaled MCCT showed that the three sequences would have a common ancestor dated only four years before the sampling date, suggesting that, unlike the gt-D, the F1b has been recently introduced in Misiones. This is consistent with the current epidemiological data from other regions of Argentina, pointing to this sgt as responsible for most of the acute and new chronic HBV infections (Barbini et al, 2013;Gallego et al, 2014;González López Ledesma et al, 2015;Pezzano et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…It is worth mentioning that almost all gt-D samples presented stop codons that preclude the HBeAg expression and one-third of them exhibit more than one mutation related to HBeAg negative phenotype. Particularly, the substitution G1896A was frequently observed in both: gt-D and sgt-F4 isolates (76.6% and 100% respectively), consistent with previous reports (González López Ledesma et al, 2015). In addition, all the F1b strains analyzed in this study displayed a wild type BCP sequence, possibly related to more recent infections, as discussed above.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations